Evaluation of the changes of the shoreline in Cua Tung in Quang Tri province before and after the construction of groin on the south riverbank of Ben Hai river - Chau, Trinh Thi Giao; Minh, Hoang Thi Binh; Lin, Hoang Ngoc (Vietnam Journal of Marine Science and Technology, 2020)
The process of erosion-sedimentation of Cua Tung, Quang Tri province has been mentioned in previous studies, but there have been no studies that apply satellite images to evaluate the changes of shoreline before and after the construction of groin along the south of Ben Hai river. This paper aims to evaluate the changes and rate of erosion - sedimentation of Cua Tung shoreline before and after the construction, using Landsat satellite images from 1990 to 2017. We used Envi 5.0 to analyse and interpret multiple-spectral Landsat satellite images in combination with analysis algorithm to identify the shoreline change over the years by adopting the ratio image method by Gathot Winasor to separate water zone and shoreline zone automatically. We then calculated the rate of shoreline changes by the function DSAS (Digital Shoreline Analysis System) proposed by Thieler et al., in Avenue programming language in ArcView software. The results showed that the process of erosion-sedimentation in Cua Tung-Quang Tri from 1990 to 2017 was divided into 6 stages in which the stage of 2000–2005 had the clearest indication in the process of erosion-sedimentation. This research has demonstrated that GIS and remote sensing technologies have been good tools to assist policy maker in their decision-making to properly evaluate erosion-sedimentation in Cua Tung- Quang Tri, so that appropriate solutions will be delivered to guarantee the local socio-economic sustainable development.